GIS-based assessment of photovoltaic solar potential on building rooftops in equatorial urban areas - Andrés Idrovo-Macancela; Marco Velecela-Zhindón; Antonio Barragán-Escandón; Esteban Zalamea-León; Danilo Mejía-Coronel (Heliyon)
Installing photovoltaic systems (PVs) on building rooftops is a viable and sustainable alternative to meet the growing demand for electricity in cities. This work develops a methodology that uses LiDAR (laser imaging detection and ranging) technology and roof footprints to obtain a three-dimensional representation of the rooftops in the urban centre of Santa Isabel (Azuay, Ecuador). This allowed the determination of characteristics such as area, slope, orientation, and received solar radiation, making it possible to calculate the rooftop's theoretical, technical, and economic photovoltaic potential. It was found that 68.8 % of the total roof surface is suitable for PV capture, with which a theoretical photovoltaic potential of 62.39 GWh can be achieved. The annual technical photovoltaic potential using silicon panels was calculated at 4.85 GWh, which could supply 4.97 times the demand of the analyzed neighbourhood. To determine the economic potential, the peak power of a solar project was calculated to match the electricity demand of the analysis area, with a levelized cost of energy of 12.37 c$/kWh. This project could prevent the emission of 6805 tons of CO₂ into the environment during its useful life. The methodology developed in this study can be replicated in other areas to determine their photovoltaic potential and contribute to the diversification and decentralization of electricity generation systems, as well as transform Ecuador's energy matrix.